2020
DOI: 10.1177/0192513x20911971
|View full text |Cite
|
Sign up to set email alerts
|

With or Without You – Starting Single-parent Families: A Qualitative Study on How Single Parents by Choice Reorganise Their Lives to Facilitate Single Parenthood from a Life Course Perspective

Abstract: Single parenthood is often approached as a problematic situation. People become single parents through divorce, separation, or bereavement and have to cope with this situation. These transitions to single parenthood lead to unforeseen problems with respect to the organization of the household. Nevertheless, there are also single parents for whom single parenthood is a positive story. These people are single parents by choice. Today, it is no longer necessary to have a partner to start a family, as people are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Regarding practitioners and people who work with single mothers after divorce, it is important to focus on motherhood ideologies. When people are reorganizing their lives after divorce, it is not only important to look at changes in household routines, but also at their role aspirations as a mother (Van Gasse and Mortelmans 2020a, 2020b, 2020c. Motherhood ideologies partially reflect the motherhood aspirations of single mothers, and this is also an important aspect in their transition to single parenthood (Taylor 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding practitioners and people who work with single mothers after divorce, it is important to focus on motherhood ideologies. When people are reorganizing their lives after divorce, it is not only important to look at changes in household routines, but also at their role aspirations as a mother (Van Gasse and Mortelmans 2020a, 2020b, 2020c. Motherhood ideologies partially reflect the motherhood aspirations of single mothers, and this is also an important aspect in their transition to single parenthood (Taylor 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we will leave this focus group to future research that should focus to the gender-specific issues of single fathers' work life balance as well. We do explicitly look into single motherhood after divorce, although other consequences of single parenthood, such as single parenthood by choice or due to bereavement also occur in Belgium (Van Gasse and Mortelmans 2020b;Walsh and McGoldrick 2013). The reasoning behind studying single motherhood after divorce or separation is due to the well-documented increase of stress levels in the period wherein single mothers reorganize their lives to start a single-parent family, illustrating the role and financial strain in this transition process (Booth and Amato 1991;Van Gasse and Mortelmans 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…While the nuclear family has traditionally been considered the standard family structure in the United States, the rise in single parent households has often been lauded as a negative phenomenon. There are, however, many avenues to becoming a single parent, some of which are a positive experience, and many people are single parents by choice [ 36 ]. Studies have demonstrated that no matter the situations leading to single parenthood, there is a clear need for policy initiatives to improve work-life balance of single mothers [ 37 ]..…”
Section: Discussionmentioning
confidence: 99%
“…All data sources were first transcribed and centrally collected following the verbatim principles, as described by Van Gasse and Mortelmans (2020aMortelmans ( , 2020b, and pseudonymized during transcription. We used NVivo to restructure the interviews and analyze the transcripts, according to the principles of grounded theory analysis (Glaser and Strauss 1967).…”
Section: Methodsmentioning
confidence: 99%
“…The gatekeeping dilemma is further complicated by doctor shopping and unmonitored fertilization. First, various studies on single motherhood by choice have suggested that fertility clinics are but one pathway to the single mother family (Van Gasse and Mortelmans 2020b;Hertz 2006;Mannis 1999). Women who can conceive without fertility treatment can opt to forgo the fertility clinic and follow an unmonitored route to planned single motherhood.…”
Section: Doctor Shopping and Unmonitored Fertilizationmentioning
confidence: 99%